Thermodynamic study of semiconducting related materials by use of EMF method with solid electrolyte - Katayama Iwao; Tanaka Toshihiro; Iida Takamichi (Journal of Mining and Metallurgy. Section B: Metallurgy)
Electromotive force method with solid electrolyte is briefly explained, and a thermodynamic study of semi conducting compound solid solution ZnTe-CdTe is picked up to show the way how thermodynamic functions of this system are obtained by several experimental methods based on our published papers and recently published data are added for comparison.